2006
DOI: 10.1295/polymj.pj2005183
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Water Adsorption Ratio Improvement of Polypropylene Fabric by Plasma Pre-treatment and Graft Polymerization

Abstract: ABSTRACT:Although the hydrophilicity of polypropylene (PP) fabric surface can be improved by plasma treatment, it would obviously decay with the storage time. In this study, the graft polymerization of acrylamide (AAm) onto the surface of PP fabric was carried out by plasma pre-treatment and subsequently induced by UV-induce surface graft polymerization to improve the long term water adsorption ratio of the substrate. During the process, peroxides formed by the plasma treatment are the major factor responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…33 The use of hexamethyl-disiloxane (HMDSO) fragmentation under plasma conditions has been studied extensively to achieve polymer layer depositions on various substrates. As an example, the successful modification of PP-fabrics could be achieved by HMDSO containing plasma and an increase in water wettability can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…33 The use of hexamethyl-disiloxane (HMDSO) fragmentation under plasma conditions has been studied extensively to achieve polymer layer depositions on various substrates. As an example, the successful modification of PP-fabrics could be achieved by HMDSO containing plasma and an increase in water wettability can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Group 1 was not submitted to any treatment; Group 2 was washed with distilled water in an ultrasound device for 12 hours; [49][50][51] and Group 3 was washed with 95% alcohol solution in a magnetic stirrer for 12 hours. 52,53 All the samples were kept at room temperature for 24 hours and were subsequently subjected to exactly the same impregnation processes. Thus, it was possible to determine whether the pretreatment results showed significant differences with the addition of VM-Theospheres in nonwovens.…”
Section: Impregnation Of the Vm-theospheres In Nonwovensmentioning
confidence: 99%
“…On one hand, this pandemic causes collapses in the healthcare system, a global setback of the economy, and a shortage of healthcare supplies in many countries. On the other hand, however, the tremendous wasted masks generated during this pandemic provide rich resources as friction materials for TENGs for two reasons: (1) commercial FFRs or medical masks are made from PP fabric, and PP is electronegative with a high charge affinity, and (2) PP fabric consists of microfiber networks with a high specific area, which is promising for applications in high-performance triboelectric materials. Although several studies on the reuse of wasted masks have been reported, they mainly focus on using these as masks again .…”
Section: Introductionmentioning
confidence: 99%